Two-component sealant, preparation method thereof and photovoltaic module
By using two-component sealant, combined with alkoxy modified polyisobutylene, calcium carbonate, silane modified magnesium hydroxide and other components, the corrosion problem of photovoltaic modules in high salt spray environments is solved, and the long-term stability and efficient performance of the module are achieved.
Patent Information
- Application Number
- CN202411716054.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
AI Technical Summary
Existing solar photovoltaic modules are susceptible to corrosion by chloride and sodium ions in high salt spray environments, resulting in reduced electrical performance or failure of the module.
A two-component sealant is used, which includes component A and component B. Component A contains alkoxy modified polyisobutylene, calcium carbonate, silane modified magnesium hydroxide and other components. Component B contains crosslinking agent, silane coupling agent and catalyst. The bonding strength is improved and the water vapor transmission rate is reduced through crosslinking reaction, and the penetration of chloride ions and sodium ions is prevented.
It effectively improves the bonding strength and salt spray corrosion resistance of photovoltaic modules, and extends the service life of the modules.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solar cells, and in particular to a two-component sealant and a preparation method thereof, and a photovoltaic module. Background Art
[0002] The core component of solar photovoltaic power generation is the solar cell. Since the solar cell itself has defects such as thinness, brittleness, and easy oxidation, it is easy to cause permanent damage when exposed to natural environments such as air and rain. Therefore, in order to realize the industrial application of solar power generation, the solar cell needs to be protectively sealed to form a solar photovoltaic module.
[0003] In recent years, there are more and more photovoltaic offshore projects. Offshore photovoltaic modules are also subjected to high salt fog, high ultraviolet and high humidity and heat environment. Especially in the high salt fog environment, once sodium chloride ions enter the interior of the module, the aluminum, lead oxide and silver on the front of the battery cell will be severely chemically corroded, causing the glass frit and aluminum in the slurry to be replaced by chloride ions and sodium ions, and the porosity in the slurry to increase. Ultimately, the electrical contact of the battery cell is destroyed, which greatly reduces the electrical performance of the module and may even cause the module to fail.
[0004] Silicone sealants are particularly suitable for protective sealing of solar cell modules due to their superior high and low temperature resistance, weather resistance, good adhesion and sealing properties. Although current silicone sealants also have a certain resistance to salt spray corrosion, in a long-term salt spray environment, chloride ions and sodium ions can easily penetrate the colloid itself and directly enter the module package, thereby affecting the electrical properties of the battery cell. Therefore, how to effectively prevent salt spray from entering the interior of photovoltaic modules and extend the service life of the modules is of great significance to the development and promotion of offshore photovoltaic new energy products. Summary of the invention
[0005] The present application provides a two-component sealant and a preparation method thereof, and a photovoltaic module to solve or alleviate the technical problems mentioned above. The two-component sealant provided by the technical solution of the present application can not only improve the bonding strength of the photovoltaic module and reduce the water vapor transmission rate, but also prevent the corrosion of external chloride ions and sodium ions on the internal batteries of the module. Applying it to the photovoltaic module can extend the service life of the photovoltaic module.
[0006] In a first aspect, an embodiment of the present application provides a two-component sealant, comprising a component A and a component B, wherein the component A comprises the following components in parts by weight: 30-60 parts by weight of alkoxy-modified polyisobutylene, 1-10 parts by weight of dimethyl silicone oil, 35-55 parts by weight of calcium carbonate, 5-20 parts by weight of silane-modified magnesium hydroxide, 0.5-3 parts by weight of fumed silica, and 0.2-2 parts by weight of a curing agent; The B component includes the following components in parts by weight: 30-60 parts by weight of alkoxy-modified polyisobutylene, 35-55 parts by weight of calcium carbonate, 5-20 parts by weight of silane-modified magnesium hydroxide, 0.5-3 parts by weight of fumed silica, 2-8 parts by weight of a crosslinking agent, 1-5 parts by weight of a silane coupling agent, and 0.05-0.5 parts by weight of a catalyst.
[0007] Optionally, the silane-modified magnesium hydroxide of component A includes one or both of aminosilane-modified magnesium hydroxide and epoxysilane-modified magnesium hydroxide; and / or The silane-modified magnesium hydroxide of the B component includes one or both of aminosilane-modified magnesium hydroxide and epoxysilane-modified magnesium hydroxide.
[0008] Optionally, the viscosity of the alkoxy-modified polyisobutylene of component A is 5000-50000 mPa·s; and / or The viscosity of the alkoxy-modified polyisobutylene of the B component is 5000-50000 mPa·s.
[0009] Optionally, the viscosity of the dimethyl silicone oil of component A is 50-300 mPa·s; and / or The viscosity of the dimethyl silicone oil of component B is 50-300 mPa·s.
[0010] Optionally, the average particle size of the calcium carbonate of component A is 50-100 nm; and / or The average particle size of the calcium carbonate of the B component is 50-100 nm.
[0011] Optionally, the specific surface area of the fumed silica of component A is 100-300m 2 / g; and / or The specific surface area of the fumed silica of component B is 100-300 m 2 / g.
[0012] Optionally, the average particle size of the silane-modified magnesium hydroxide of component A is 1-10 μm; and / or The average particle size of the silane-modified magnesium hydroxide of the B component is 1-10 μm.
[0013] Optionally, in the component A, the mass ratio of silane-modified magnesium hydroxide to alkoxy-modified polyisobutylene is 0.1-0.6; and / or In the B component, the mass ratio of the silane-modified magnesium hydroxide to the alkoxy-modified polyisobutylene is 0.1-0.6.
[0014] Optionally, the curing agent includes one or more of water, hydrated aluminum oxide, hydrated calcium chloride, and hydrated calcium sulfate; and / or The crosslinking agent includes one or more of methyltrimethoxysilane, dimethyldiethoxysilane, tetraethoxysilane, vinyltriethoxysilane, propyltrimethoxysilane, and methyltriethoxysilane; and / or The silane coupling agent includes one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane; and / or The catalyst includes one or more of dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin diacetate, and stannous octoate.
[0015] In a second aspect, an embodiment of the present application provides a method for preparing any of the above-mentioned two-component sealants, comprising: 30-60 parts by weight of alkoxy-modified polyisobutylene, 1-10 parts by weight of dimethyl silicone oil, 35-55 parts by weight of calcium carbonate, 5-20 parts by weight of silane-modified magnesium hydroxide, and 0.5-3 parts by weight of fumed silica are uniformly mixed to obtain a first mixture; Mixing 0.2-2 parts by weight of a curing agent with the first mixture to obtain component A; 30-60 parts by weight of alkoxy-modified polyisobutylene, 35-55 parts by weight of calcium carbonate, 5-20 parts by weight of silane-modified magnesium hydroxide, and 0.5-3 parts by weight of fumed silica are uniformly mixed to obtain a second mixture; Mixing 2-8 parts by weight of a cross-linking agent with the second mixture to react to obtain a third mixture; 1-5 parts by weight of a silane coupling agent and 0.05-0.5 parts by weight of a catalyst are uniformly mixed with the third mixture to obtain a B component.
[0016] In a third aspect, an embodiment of the present application provides a photovoltaic module, comprising any of the above-mentioned two-component sealants.
[0017] The above technical solution adopted in the embodiment of the present application may have the following advantages: The two-component sealant of the embodiment of the present application includes component A and component B, both of which include alkoxy-modified polyisobutylene, calcium carbonate, silane-modified magnesium hydroxide, and fumed silica, and component A also includes dimethyl silicone oil, and component B also includes a crosslinking agent, a silane coupling agent, and a catalyst. Under the action of the air environment and the catalyst, the crosslinking agent, the silane coupling agent, and the alkoxy-modified polyisobutylene react with each other to improve the bonding strength of the two-component sealant; alkoxy-modified polyisobutylene is used as the main raw material, and its molecular chain side methyl groups are densely arranged and arranged regularly, which limits the thermal motion of the molecules and reduces the water vapor permeability; silane-modified magnesium hydroxide has good dispersibility in the two-component sealant system, can better absorb polymers, form wrapped structural units, improve the order of the polymer structure, reduce structural defects in the sealant system, and reduce the permeability of chloride ions and sodium ions to the two-component sealant system, preventing the corrosion of external chloride ions and sodium ions to the batteries inside the assembly. In addition, component A also includes a curing agent. When component A and component B are mixed, the curing agent can accelerate the reaction of the cross-linking agent, silane coupling agent and alkoxy-modified polyisobutylene, thereby effectively improving the internal curing speed of the two-component sealant and avoiding secondary glue overflow caused by slow internal curing. Moreover, its curing depth is not affected by its own water-blocking properties, which can avoid the risk of secondary glue overflow in the later stage. DETAILED DESCRIPTION
[0018] The embodiments of the present application are described in detail below, which are only used to explain the present application and cannot be understood as limiting the present application. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other in the absence of conflict.
[0019] The present application embodiment provides a two-component sealant, including component A and component B, wherein: The A component comprises the following components in parts by weight: 30-60 parts by weight of alkoxy-modified polyisobutylene, 1-10 parts by weight of dimethyl silicone oil, 35-55 parts by weight of calcium carbonate, 5-20 parts by weight of silane-modified magnesium hydroxide, 0.5-3 parts by weight of fumed silica, and 0.2-2 parts by weight of a curing agent; The B component includes the following components in parts by weight: 30-60 parts by weight of alkoxy-modified polyisobutylene, 35-55 parts by weight of calcium carbonate, 5-20 parts by weight of silane-modified magnesium hydroxide, 0.5-3 parts by weight of fumed silica, 2-8 parts by weight of a crosslinking agent, 1-5 parts by weight of a silane coupling agent, and 0.05-0.5 parts by weight of a catalyst.
[0020] The functions and contents of each component in the two-component sealant are as follows: Alkoxy-modified polyisobutylene is the main component of two-component sealant. The methyl groups on the side of its molecular chain are densely arranged and arranged regularly, which limits the thermal motion of the molecules and reduces the water vapor transmission rate. At 38°C, the water vapor transmission rate is only 2g / m 2 / 24h (the water vapor transmission rate of existing photovoltaic sealants is greater than or equal to 50g / m 2 / 24h), can not only improve the mechanical properties of the two-component sealant, but also improve the salt spray corrosion resistance of the two-component sealant. An appropriate amount of alkoxy-modified polyisobutylene is conducive to compounding with other ingredients, thereby improving the mechanical properties of the two-component sealant. In the two-component sealant of the present application, the content of alkoxy-modified polyisobutylene in component A is 30-60 parts by weight, preferably 40-50 parts by weight; the content of alkoxy-modified polyisobutylene in component B is 30-60 parts by weight, preferably 40-50 parts by weight.
[0021] Dimethyl silicone oil can improve the rheological properties of two-component sealants, improve the extrusion properties of two-component sealants, and thus improve the quality of the finished two-component sealants. The amount of dimethyl silicone oil should not be too large, otherwise it will increase the surface drying time of the two-component sealant and reduce the mechanical properties of the photovoltaic module; the amount of dimethyl silicone oil should not be too small, otherwise the two-component sealant cannot achieve the required rheological properties. In the two-component sealant of the present application, component A contains dimethyl silicone oil, and the content of dimethyl silicone oil is 1-10 parts by weight, preferably 3-8 parts by weight.
[0022] Calcium carbonate is a reinforcing filler that can improve the physical properties of two-component sealants, enhance the hardness and wear resistance of two-component sealants, and can also improve the tensile strength of two-component sealants and reduce material costs. In two-component sealants, if the amount of calcium carbonate used is too large, the calcium carbonate particles will aggregate, affecting the mechanical properties and rheological properties of the two-component sealant; if the amount of calcium carbonate used is too small, its reinforcing effect cannot be exerted. In the two-component sealant of the present application, the content of calcium carbonate in component A is 35-55 parts by weight, preferably 40-50 parts by weight; the content of calcium carbonate in component B is 35-55 parts by weight, preferably 40-50 parts by weight.
[0023] Silane-modified magnesium hydroxide has good dispersibility in two-component sealants, can better absorb polymers, form wrapped structural units, improve the order of polymer structures, and reduce structural defects in the sealant system; secondly, magnesium hydroxide has a layered bimetallic oxide structure, and the complex anti-permeation diffusion path formed by its layer structure greatly reduces the penetration of chloride ions and sodium ions to the sealant system. At the same time, the anions between its layers are easily replaced by other anions, and it has good anion exchange properties. It can absorb chloride ions in the environment, thereby preventing the corrosion of chloride ions, and can better protect the internal batteries of the components from corrosion by external chloride ions and sodium ions, further improving the salt spray corrosion resistance of the two-component sealant. Silane-modified magnesium hydroxide is magnesium hydroxide modified by silane. Due to the presence of silane groups, it can be better dissolved in the two-component sealant system. In the two-component sealant of the present application, the content of silane-modified magnesium hydroxide in component A is 5-20 parts by weight, preferably 10-15 parts by weight; the content of silane-modified magnesium hydroxide in component B is 5-20 parts by weight, preferably 10-15 parts by weight.
[0024] Fumed silica is also a reinforcing filler, which can improve the physical properties of the two-component sealant, enhance the hardness and wear resistance of the two-component sealant, and also improve the tensile strength of the two-component sealant. In the two-component sealant of the present application, the content of fumed silica in component A is 0.5-3 parts by weight, preferably 1-2 parts by weight; the content of fumed silica in component B is 0.5-3 parts by weight, preferably 1-2 parts by weight.
[0025] The crosslinking agent contains multiple functional groups and can form chemical bonds between linear or slightly branched macromolecules, so that the alkoxy-modified polyisobutylene and the silane coupling agent are crosslinked to form a three-dimensional network structure, thereby improving the molding speed, mechanical strength, wear resistance, and high temperature resistance of the two-component sealant, and improving the adsorption performance and softness of the two-component sealant. If the amount of the crosslinking agent is too large, the crosslinking density of the two-component sealant will be too high, making the two-component sealant too hard and brittle, thereby reducing its flexibility and impact resistance; if the amount of the crosslinking agent is too small, the cohesion of the two-component sealant will be reduced. In the two-component sealant of the present application, component B contains a crosslinking agent, and the content of the crosslinking agent is 2-8 parts by weight, preferably 3-6 parts by weight.
[0026] Silane coupling agents contain silicon-hydrogen bonds. When contacting the adherend material, the silane coupling agent reacts with the adherend and alkoxy-modified polyisobutylene through the silicon-philic group to form a strong and durable covalent bond, thereby improving the interfacial adhesion, weather resistance, chemical corrosion resistance, and improving wettability and dispersibility. Too much silane coupling agent will increase the viscosity of the two-component sealant, which is not conducive to rheology; too little silane coupling agent will lead to insufficient bonding strength of the two-component sealant. In the two-component sealant of the present application, component B contains a silane coupling agent, and the content of the silane coupling agent is 1-5 parts by weight, preferably 2-4 parts by weight.
[0027] The catalyst can reduce the activation energy of the reaction, thereby accelerating the curing reaction, shortening the curing time of the two-component sealant, and improving the strength of the two-component sealant. If the amount of catalyst is too much, it is difficult to control the reaction process, affecting the quality of the product; if the amount of catalyst is too little, the curing time cannot be controlled within a reasonable range, affecting production efficiency. In the two-component sealant of the present application, component B contains a catalyst, and the content of the catalyst is 0.05-0.5 parts by weight, preferably 0.1-0.3 parts by weight.
[0028] When component A and component B are mixed, the alkoxy-modified polyisobutylene reacts with the crosslinking agent under the action of the catalyst and is cured, wherein the curing agent can accelerate the curing reaction rate and shorten the curing time, thereby achieving rapid curing. In the two-component sealant of the present application, component A contains a curing agent, and the content of the curing agent is 0.2-2 parts by weight, preferably 0.5-1.5 parts by weight.
[0029] In some embodiments, the silane-modified magnesium hydroxide of component A includes one or both of aminosilane-modified magnesium hydroxide and epoxysilane-modified magnesium hydroxide; and / or The silane-modified magnesium hydroxide of the B component includes one or both of aminosilane-modified magnesium hydroxide and epoxysilane-modified magnesium hydroxide.
[0030] Silane-modified magnesium hydroxide refers to a compound in which magnesium hydroxide is modified by silane using a silane coupling agent. The silane-modified magnesium hydroxide of component A and component B respectively and independently includes one or two of aminosilane-modified magnesium hydroxide and epoxysilane-modified magnesium hydroxide; wherein the silane coupling agent may be γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane or γ-methacryloxypropyltrimethoxysilane.
[0031] In some embodiments, the viscosity of the alkoxy-modified polyisobutylene of component A is 5000-50000 mPa·s; and / or The viscosity of the alkoxy-modified polyisobutylene of the B component is 5000-50000 mPa·s.
[0032] The larger the molecular weight of the alkoxy-modified polyisobutylene, the higher its viscosity, which generally means that the molecular chain is longer and the interaction between molecules is stronger. Higher viscosity may help improve the cohesion and bonding properties of the two-component sealant, but too high viscosity will affect the fluidity of the two-component sealant. When the viscosity of the alkoxy-modified polyisobutylene of component A and the alkoxy-modified polyisobutylene of component B are respectively and independently 5000-50000 mPa·s, the two-component sealant has better cohesion, bonding properties and fluidity. Specifically, the viscosity of the alkoxy-modified polyisobutylene of component A and the viscosity of the alkoxy-modified polyisobutylene of component B may be respectively and independently 5000 Pa·s, 10000 Pa·s, 15000 mPa·s, 20000 Pa·s, 25000 Pa·s, 30000 Pa·s, 35000 mPa·s, 40000 Pa·s, 45000 Pa·s or 50000 mPa·s.
[0033] In some embodiments, the viscosity of the dimethyl silicone oil of component A is 50-300 mPa·s; and / or The viscosity of the dimethyl silicone oil of component B is 50-300 mPa·s.
[0034] In a two-component sealant, if the viscosity of dimethyl silicone oil is too high, it will increase the viscosity of the two-component sealant, thereby affecting its fluidity and construction performance; if the viscosity of dimethyl silicone oil is too low, it will cause the bonding strength and cohesion of the two-component sealant to decrease. When the viscosity of the dimethyl silicone oil of component A and the viscosity of the dimethyl silicone oil of component B are respectively and independently 50-300mPa·s, the two-component sealant can have both fluidity and bonding strength. Specifically, the viscosity of the dimethyl silicone oil of component A and the viscosity of the dimethyl silicone oil of component B can be respectively and independently 50Pa·s, 100Pa·s, 150mPa·s, 200Pa·s, 250mPa·s or 300mPa·s.
[0035] In some embodiments, the average particle size of the calcium carbonate of component A is 50-100 nm; and / or The average particle size of the calcium carbonate of the B component is 50-100 nm.
[0036] The average particle size of calcium carbonate has an important influence on the tensile strength of the two-component sealant. The tensile strength will increase as the average particle size decreases, but too small an average particle size will reduce its dispersion performance and affect the extrusion of the two-component sealant. When the average particle size of the calcium carbonate of component A and the average particle size of the calcium carbonate of component B are respectively and independently 50-100nm, not only the extrusion performance of the two-component sealant is suitable for the production line, but also the two-component sealant can be guaranteed to have a higher tensile strength. Specifically, the average particle size of the calcium carbonate of component A and the average particle size of the calcium carbonate of component B can be respectively and independently 50nm, 60nm, 70nm, 80nm, 90nm or 100nm.
[0037] In some embodiments, the specific surface area of the fumed silica of component A is 100-300 m 2 / g; and / or The specific surface area of the fumed silica of component B is 100-300 m 2 / g.
[0038] The specific surface area of fumed silica has an important influence on the tensile strength of two-component sealants. The tensile strength increases with the increase of specific surface area. However, too large a specific surface area will reduce its dispersion performance and affect the extrusion of the two-component sealant. When the specific surface area of the fumed silica of component A and the specific surface area of the fumed silica of component B are 100-300m 2 When the extrusion performance of the two-component sealant is suitable for the production line, the two-component sealant can also have a high tensile strength. Specifically, the specific surface area of the fumed silica of component A and the specific surface area of the fumed silica of component B can be 100 m 2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g or 300m 2 / g.
[0039] In some embodiments, the average particle size of the silane-modified magnesium hydroxide of component A is 1-10 μm; and / or The average particle size of the silane-modified magnesium hydroxide of the B component is 1-10 μm.
[0040] The average particle size of silane-modified magnesium hydroxide has an important influence on the barrier effect and tensile strength of the two-component sealant. The barrier effect will increase with the increase of the average particle size, but too large an average particle size will reduce the tensile strength and affect the colloidal strength of the two-component sealant. When the average particle size of the silane-modified magnesium hydroxide of component A and the average particle size of the silane-modified magnesium hydroxide of component B are respectively and independently 1-10μm, not only the two-component sealant has a good barrier effect, but also can ensure that the two-component sealant has a high tensile strength. Specifically, the average particle size of the silane-modified magnesium hydroxide of component A and the average particle size of the silane-modified magnesium hydroxide of component B can be respectively and independently 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm.
[0041] In some embodiments, in the A component, the mass ratio of silane-modified magnesium hydroxide to alkoxy-modified polyisobutylene is 0.1-0.6; and / or In the B component, the mass ratio of the silane-modified magnesium hydroxide to the alkoxy-modified polyisobutylene is 0.1-0.6.
[0042] In component A or component B, the mass ratio of silane-modified magnesium hydroxide to alkoxy-modified polyisobutylene is controlled to be 0.1-0.6, which can further improve the anti-salt spray performance of the two-component sealant without affecting the mechanical properties of the two-component sealant. Specifically, the mass ratio of silane-modified magnesium hydroxide to alkoxy-modified polyisobutylene in component A and component B is respectively and independently 0.1, 0.2, 0.3, 0.4, 0.5 or 0.6.
[0043] In some embodiments, the curing agent includes one or more of water, hydrated aluminum oxide, hydrated calcium chloride, and hydrated calcium sulfate, wherein the water may be deionized water.
[0044] When two-component sealants are cured, water vapor is required. When the curing agent of component A includes one or more of water, hydrated aluminum oxide, hydrated calcium chloride, and hydrated calcium sulfate, the curing agent can not only promote the hydrolysis of the cross-linking agent and the silane coupling agent, but also help the cross-linking agent and the silane coupling agent to react with the terminal hydroxyl polydimethylsiloxane under the action of the catalyst, so that the two-component sealant can be cured quickly.
[0045] In some embodiments, the crosslinking agent includes one or more of methyltrimethoxysilane, dimethyldiethoxysilane, tetraethoxysilane, vinyltriethoxysilane, propyltrimethoxysilane, and methyltriethoxysilane. These crosslinking agents have good compatibility with alkoxy-modified polyisobutylene, react more fully with alkoxy-modified polyisobutylene, and can play a bridging role between linear molecules, thereby allowing multiple linear molecules or lightly branched macromolecules and polymers to bond and crosslink to form a three-dimensional network structure, promote or regulate the formation of covalent bonds or ionic bonds between polymer molecular chains, and help improve the colloid strength of the two-component sealant.
[0046] In some embodiments, the silane coupling agent includes one or more of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane. These silane coupling agents have good compatibility with alkoxy-modified polyisobutylene and react fully with alkoxy-modified polyisobutylene, which is beneficial to improving the bonding strength of the two-component sealant.
[0047] In some embodiments, the catalyst includes one or more of dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin diacetate, and stannous octoate. These catalysts can significantly accelerate the curing reaction of the two-component sealant, thereby improving the bonding effect.
[0048] The embodiment of the present application provides a method for preparing a two-component sealant, which is used to prepare the two-component sealant described in any of the above embodiments, including: a method for preparing component A and a method for preparing component B.
[0049] The preparation method of component A comprises: 30-60 parts by weight of alkoxy-modified polyisobutylene, 1-10 parts by weight of dimethyl silicone oil, 35-55 parts by weight of calcium carbonate, 5-20 parts by weight of silane-modified magnesium hydroxide, and 0.5-3 parts by weight of fumed silica are uniformly mixed to obtain a first mixture; 0.2-2 parts by weight of a curing agent is uniformly mixed with the first mixture to obtain component A.
[0050] The preparation method of component B comprises: 30-60 parts by weight of alkoxy-modified polyisobutylene, 35-55 parts by weight of calcium carbonate, 5-20 parts by weight of silane-modified magnesium hydroxide, and 0.5-3 parts by weight of fumed silica are uniformly mixed to obtain a second mixture; Mixing 2-8 parts by weight of a cross-linking agent with the second mixture to react to obtain a third mixture; 1-5 parts by weight of a silane coupling agent and 0.05-0.5 parts by weight of a catalyst are uniformly mixed with the third mixture to obtain a B component.
[0051] In some embodiments, the method for preparing component A comprises: 30-60 parts by weight of alkoxy-modified polyisobutylene, 1-10 parts by weight of dimethyl silicone oil, 35-55 parts by weight of calcium carbonate, 5-20 parts by weight of silane-modified magnesium hydroxide, and 0.5-3 parts by weight of fumed silica are stirred for 1-3 hours (for example, 1 hour, 2 hours, or 3 hours) in an environment with a temperature of 120-130° C. (for example, 120° C., 125° C., or 130° C.) and a vacuum degree of less than or equal to -0.095 MPa (for example, -0.10 MPa or -0.095 MPa) to obtain a first mixture; 0.2-2 parts by weight of the curing agent and the first mixture are stirred for 10-20 minutes (for example, 10 minutes, 15 minutes or 20 minutes) in an environment with a vacuum degree of -0.10 MPa to -0.09 MPa (for example, -0.10 MPa, -0.095 MPa or -0.09 MPa) to mix evenly to obtain component A.
[0052] In some embodiments, the method for preparing component B comprises: 30-60 parts by weight of alkoxy-modified polyisobutylene, 35-55 parts by weight of calcium carbonate, 5-20 parts by weight of silane-modified magnesium hydroxide, and 0.5-3 parts by weight of fumed silica are stirred for 1-3 hours (for example, 1 hour, 2 hours, or 3 hours) in an environment with a temperature of 120-130° C. (for example, 120° C., 125° C., or 130° C.) and a vacuum degree of less than or equal to -0.095 MPa (for example, -0.10 MPa or -0.095 MPa) to obtain a second mixture; 2-8 parts by weight of the cross-linking agent and the second mixture are stirred and reacted for 20-40 minutes (e.g., 20 minutes, 30 minutes or 40 minutes) to obtain a third mixture; 1-5 parts by weight of a silane coupling agent, 0.05-0.5 parts by weight of a catalyst and the third mixture are stirred for 20-40 minutes (e.g., 20 minutes, 30 minutes or 40 minutes) in an environment with a vacuum degree of -0.10 MPa to -0.09 MPa (e.g., -0.10 MPa, -0.095 MPa or -0.09 MPa) to mix uniformly to obtain component B.
[0053] It should be noted that there is no fixed order for the preparation of component A and component B, that is, A can be prepared first and then B; B can be prepared first and then A; or A and B can be prepared at the same time. The two-component sealant of the embodiment of the present application can be obtained without mixing component A and component B, but component A and component B are mixed according to a mass ratio of 1:2-2:1 (for example, 1:2, 1:1 or 2:1) during use.
[0054] The following specific examples further illustrate the present application in detail, but should not be construed as limiting the present application. Without departing from the spirit and substance of the present application, modifications or substitutions made to the methods, steps or conditions of the present application are within the scope of the present application. The following further provides the formulas of the two-component sealants of Examples 1-8 of the present application and Comparative Example 1 in a tabular manner, and the specific formulas are shown in Table 1.
[0055] Table 1
[0056] In Examples 1 to 8 of the present application, the viscosity of the alkoxy-modified polyisobutylene of component A is 5000-50000 mPa·s, the viscosity of the alkoxy-modified polyisobutylene of component B is 5000-50000 mPa·s, the viscosity of the dimethyl silicone oil of component A is 50-300 mPa·s, the viscosity of the dimethyl silicone oil of component B is 50-300 mPa·s, the average particle size of the calcium carbonate of component A is 50-100 nm, the average particle size of the calcium carbonate of component B is 50-100 nm, and the specific surface area of the fumed silica of component A is 100-300 m 2 / g, the specific surface area of the fumed silica of component B is 100-300m 2 / g, the average particle size of the silane-modified magnesium hydroxide of component A is 1-10μm, the average particle size of the silane-modified magnesium hydroxide of component B is 1-10μm, the curing agent includes one or more of water, hydrated aluminum oxide, hydrated calcium chloride, and hydrated calcium sulfate, the cross-linking agent includes one or more of methyltrimethoxysilane, dimethyldiethoxysilane, tetraethoxysilane, vinyltriethoxysilane, propyltrimethoxysilane, and methyltriethoxysilane, the silane coupling agent includes one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and the catalyst includes one or more of dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin diacetate, and stannous octoate.
[0057] The preparation methods of Examples 1 to 8 include: Preparation of component A: stirring corresponding weight portions of alkoxy-modified polyisobutylene, dimethyl silicone oil, calcium carbonate, silane-modified magnesium hydroxide, and fumed silica for 1-3 hours in an environment with a temperature of 120-130° C. and a vacuum degree of less than or equal to -0.095 MPa to obtain a first mixture; Stir the curing agent and the first mixture in corresponding weight portions in an environment with a vacuum degree of -0.10 MPa to -0.09 MPa for 10 to 20 minutes to mix them evenly to obtain component A; Preparation of component B: stirring corresponding weight portions of alkoxy-modified polyisobutylene, calcium carbonate, silane-modified magnesium hydroxide, and fumed silica for 1-3 hours in an environment with a temperature of 120-130° C. and a vacuum degree of less than or equal to -0.095 MPa to obtain a second mixture; Add corresponding weight portions of the cross-linking agent and the second mixture, stirring and reacting for 20-40 minutes to obtain a third mixture; The corresponding weight portions of the silane coupling agent, the catalyst and the third mixture are stirred for 20-40 minutes in an environment with a vacuum degree of -0.10 MPa to -0.09 MPa to mix them evenly to obtain component B.
[0058] When using the two-component sealant of Example 1 to Example 8, component A and component B are mixed in a mass ratio of 1:1.
[0059] In order to further illustrate the technical effects of the embodiments of the present application, the present application also provides Comparative Example 1, Comparative Example 2 and Comparative Example 3. The specific formulas of the two-component sealants of Comparative Examples 1 to 3 are as follows.
[0060] Comparative Example 1 The formula and preparation method of Comparative Example 1 are similar to those of Example 1, except that hydroxy-terminated polydimethylsiloxane is used in Comparative Example 1 instead of alkoxy-terminated polyisobutylene.
[0061] Comparative Example 2 The formula and preparation method of Comparative Example 2 are similar to those of Example 1, except that Comparative Example 2 does not include silane-free modified magnesium hydroxide.
[0062] Comparative Example 3 The formula and preparation method of Comparative Example 3 are similar to those of Example 1, except that hydroxy-terminated polydimethylsiloxane is used instead of alkoxy-terminated polyisobutylene in Comparative Example 3, and silane-free modified magnesium hydroxide is not included.
[0063] Performance Testing The performance tests of the two-component sealants of Examples 1-8 and Comparative Examples 1-3 of the present application are as follows. The hardness of the two-component sealants is tested according to the national standard GB / T 531; the tensile strength of the two-component sealants is tested according to the national standard GB / T 528; the shear strength (anodized aluminum profile) of the two-component sealants is tested according to the national standard GB / T 7124; the water vapor transmission rate of the two-component sealants is tested according to the national standard GB / T 1037; the salt spray corrosion resistance of the two-component sealants is tested according to the national standard GB / T 1771-2007; the specific test results are shown in Table 2.
[0064] Table 2
[0065] The test results in Table 2 show that the hardness, tensile strength, and shear strength of the two-component sealants of Examples 1-8 of the present application are similar to those of the sealants of Comparative Examples 1-3, and both can meet market demand. Compared with Comparative Examples 1-3, the two-component sealants of Examples 1-8 of the present application have lower water vapor permeability and good salt spray corrosion resistance. After 1500h of salt spray resistance test, the surface of the steel plate is still intact. The two-component sealants of the present application embodiments are applied to photovoltaic modules to extend the service life of photovoltaic modules.
[0066] In summary, the two-component sealant of the embodiment of the present application includes component A and component B, both of which include alkoxy-modified polyisobutylene, calcium carbonate, silane-modified magnesium hydroxide, and fumed silica, and the A combination also includes dimethyl silicone oil, and the B component also includes a crosslinking agent, a silane coupling agent, and a catalyst. Under the action of the air environment and the catalyst, the crosslinking agent, the silane coupling agent, and the alkoxy-modified polyisobutylene react with each other to improve the bonding strength of the two-component sealant; alkoxy-modified polyisobutylene is used as the main raw material, and the methyl groups on the side of its molecular chain are densely arranged and arranged regularly to limit the thermal motion of the molecules and reduce the water vapor permeability; silane-modified magnesium hydroxide has good dispersibility in the two-component sealant system, can better absorb polymers, form wrapped structural units, improve the order of the polymer structure, reduce structural defects in the sealant system, and reduce the permeability of chloride ions and sodium ions to the two-component sealant system, preventing the corrosion of external chloride ions and sodium ions to the batteries inside the assembly. In addition, component A also includes a curing agent. When component A and component B are mixed, the curing agent can accelerate the reaction of the cross-linking agent, silane coupling agent and alkoxy-modified polyisobutylene, thereby effectively improving the internal curing speed of the two-component sealant and avoiding secondary glue overflow caused by slow internal curing. Moreover, its curing depth is not affected by its own water-blocking properties, which can avoid the risk of secondary glue overflow in the later stage.
[0067] The embodiment of the present application also provides a photovoltaic module, including the two-component sealant described in any of the above embodiments. The photovoltaic module also includes a laminate and a photovoltaic frame, and the two-component sealant bonds the laminate and the photovoltaic frame to ensure the performance and quality of the photovoltaic module. During the preparation of the photovoltaic module, component A and component B in the two-component sealant are mixed in a mass ratio of 1:2-2:1, and are immediately used to bond the laminate and the photovoltaic frame after mixing.
[0068] The embodiment of the present application also provides a photovoltaic system, including the photovoltaic components provided in the above embodiment. The advantages of the above photovoltaic components are also possessed by the photovoltaic system, which will not be repeated here. The above photovoltaic system has a wide range of applications, not only limited to photovoltaic power stations, such as ground power stations, rooftop power stations and water power stations, but also includes various equipment and devices that use solar energy to generate electricity, such as user solar power supplies, solar street lights, solar cars and solar buildings. Of course, it can be understood that the application scenarios of the photovoltaic system are not limited to this, that is to say, the photovoltaic system can be used in all fields where solar energy is required for power generation. Taking the photovoltaic power generation system network as an example, the photovoltaic system may include a photovoltaic array, a junction box and an inverter. The photovoltaic array may be an array combination of multiple photovoltaic components. For example, multiple photovoltaic components may form multiple photovoltaic arrays. The photovoltaic array is connected to a junction box. The junction box can converge the current generated by the photovoltaic array. The converged current flows through the inverter and is converted into the alternating current required by the mains power grid, and then connected to the mains network to realize solar power supply.
[0069] It should be noted that the terms "first", "second", "third", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0070] It should be noted that: in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device that includes the element.
[0071] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, please refer to the relevant description of other embodiments. The above embodiments are only used to illustrate the technical solution of the present application, rather than to limit it. Although the present application is described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that it is still possible to modify the technical solutions recorded in the aforementioned embodiments, or to replace some of the technical features therein by equivalents; and these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.
[0072] It should also be noted that "one embodiment", "another embodiment", "embodiment", etc. mentioned in this application refer to the specific features, structures or characteristics described in conjunction with the embodiment included in at least one embodiment generally described in this application. The same expression appearing in multiple places in the specification does not necessarily refer to the same embodiment. Further, when describing a specific feature, structure or characteristic in conjunction with any embodiment, it is claimed that the realization of such feature, structure or characteristic in conjunction with other embodiments also falls within the scope of this application.
Claims
1. A two-component sealant, characterized in that: It includes component A and component B, wherein: The A component comprises the following components in parts by weight: 30-60 parts by weight of alkoxy-modified polyisobutylene, 1-10 parts by weight of dimethyl silicone oil, 35-55 parts by weight of calcium carbonate, 5-20 parts by weight of silane-modified magnesium hydroxide, 0.5-3 parts by weight of fumed silica, and 0.2-2 parts by weight of a curing agent; The B component includes the following components in parts by weight: 30-60 parts by weight of alkoxy-modified polyisobutylene, 35-55 parts by weight of calcium carbonate, 5-20 parts by weight of silane-modified magnesium hydroxide, 0.5-3 parts by weight of fumed silica, 2-8 parts by weight of a crosslinking agent, 1-5 parts by weight of a silane coupling agent, and 0.05-0.5 parts by weight of a catalyst.
2. The two-component sealant according to claim 1, characterized in that: The silane-modified magnesium hydroxide of component A includes one or both of aminosilane-modified magnesium hydroxide and epoxysilane-modified magnesium hydroxide; and / or The silane-modified magnesium hydroxide of the B component includes one or both of aminosilane-modified magnesium hydroxide and epoxysilane-modified magnesium hydroxide.
3. The two-component sealant according to claim 1, characterized in that: The viscosity of the alkoxy-modified polyisobutylene of component A is 5000-50000 mPa·s; and / or The viscosity of the alkoxy-modified polyisobutylene of the B component is 5000-50000 mPa·s.
4. The two-component sealant according to claim 1, characterized in that: The viscosity of the dimethyl silicone oil of component A is 50-300 mPa·s; and / or The viscosity of the dimethyl silicone oil of component B is 50-300 mPa·s.
5. The two-component sealant according to claim 1, characterized in that: The average particle size of the calcium carbonate of component A is 50-100 nm; and / or The average particle size of the calcium carbonate of the B component is 50-100 nm.
6. The two-component sealant according to claim 1, characterized in that: The specific surface area of the fumed silica of component A is 100-300 m 2 / g; and / or The specific surface area of the fumed silica of component B is 100-300 m 2 / g.
7. The two-component sealant according to claim 1, characterized in that: The average particle size of the silane-modified magnesium hydroxide of component A is 1-10 μm; and / or The average particle size of the silane-modified magnesium hydroxide of the B component is 1-10 μm.
8. The two-component sealant according to claim 1, characterized in that: In the component A, the mass ratio of silane-modified magnesium hydroxide to alkoxy-modified polyisobutylene is 0.1-0.6; and / or In the B component, the mass ratio of the silane-modified magnesium hydroxide to the alkoxy-modified polyisobutylene is 0.1-0.
6.
9. The two-component sealant according to any one of claims 1 to 8, characterized in that: The curing agent includes one or more of water, hydrated aluminum oxide, hydrated calcium chloride, and hydrated calcium sulfate; and / or The crosslinking agent includes one or more of methyltrimethoxysilane, dimethyldiethoxysilane, tetraethoxysilane, vinyltriethoxysilane, propyltrimethoxysilane, and methyltriethoxysilane; and / or The silane coupling agent includes one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane; and / or The catalyst includes one or more of dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin diacetate, and stannous octoate.
10. A method for preparing a two-component sealant according to any one of claims 1 to 9, characterized in that: include: 30-60 parts by weight of alkoxy-modified polyisobutylene, 1-10 parts by weight of dimethyl silicone oil, 35-55 parts by weight of calcium carbonate, 5-20 parts by weight of silane-modified magnesium hydroxide, and 0.5-3 parts by weight of fumed silica are uniformly mixed to obtain a first mixture; Mixing 0.2-2 parts by weight of a curing agent with the first mixture to obtain component A; 30-60 parts by weight of alkoxy-modified polyisobutylene, 35-55 parts by weight of calcium carbonate, 5-20 parts by weight of silane-modified magnesium hydroxide, and 0.5-3 parts by weight of fumed silica are uniformly mixed to obtain a second mixture; Mixing 2-8 parts by weight of a cross-linking agent with the second mixture to react to obtain a third mixture; 1-5 parts by weight of a silane coupling agent and 0.05-0.5 parts by weight of a catalyst are uniformly mixed with the third mixture to obtain a B component.
11. A photovoltaic module, characterized in that: It comprises a two-component sealant as claimed in any one of claims 1 to 9.